Serological tests and polymerase chain reaction for detection of Toxoplasma gondii infection in women attending for premarital examination - Bakre, Hawre Mustafa (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Human infection with toxoplasmosis is common and is usually asymptomatic, and congenital form is one of the most important clinical aspects of this disease. This study aimed to determine anti-toxoplasma antibodies, and Toxoplasma DNA in premarital women referred to Mammon Dabax health centers and to design prevention policies after marriage and during their pregnancy. Methods: One hundred fifty premarital women who were examined for pre-marriage laboratory testing were enrolled in this cross-sectional study. Blood samples were tested for specific anti-toxoplasma IgM and IgG antibodies using an enzyme-linked immuno-sorbent assay (ELISA) and detection of B1 gene of T. gondii by PCR. Results: Of 150 sera examined of premarital female 35 (23.3%) were seropositive for anti-toxoplasma antibodies by latex agglutination test. Using ELISA test, 8 (5.3%) of the sera examined were seropositive for anti-toxoplasma IgM; meanwhile, 23 (15.3%) sera were positive for anti-toxoplasma IgG. The ELISA test finding for anti-toxoplasma IgM and IgG of the total sera examined were subsequently subjected to PCR. Thus, PCR analysis for detecting T. gondii DNA in the blood of premarital female was positive in 15 (10%) of the total DNA samples. Of these 15 positive PCR when correlated with positive ELISA finding 7 (46.6%) and 4 (26.6%) blood samples were positive for anti-toxoplasma IgM and anti-toxoplasma IgG, respectively. Conclusion: PCR assay has an advantage in the detection of recent and active infections as reflection or marker for T.gondii parasitemia. ELISA can be used as a highly sensitive screening test while IgM anti-toxoplasma antibody positive is not enough to confirm recent infection as the false negative is high.